A novel biosensing platform for detection of glaucoma biomarker GDF15 via an integrated BLI-ELASA strategy. (March 2023) - Gao, Shunxiang; Li, Qian; Zhang, Shenghai; Sun, Xinghuai; Zhou, Hong; Wang, Zhongfeng; Wu, Jihong
Abstract: Glaucoma is a leading cause of irreversible blindness worldwide. Early discovery and prioritized intervention significantly impact its prognosis. Precise monitoring of the biomarker GDF15 contributes towards effective diagnosis and assessment of glaucoma. In this study, we demonstrate that GDF15 monitoring can also aid screening for glaucoma risk and early diagnosis. We obtained an aptamer (APT2TM) with high affinity, high specificity, and high stability for binding to both human-derived and rat-derived GDF15. Simulation results showed that the binding capabilities of APT2TM are mainly affected by the interplay between van der Waals forces and polar solvation energy, and that salt bridges and hydrogen bonds play critical roles. We then integrated an enzyme-linked aptamer sandwich assay (ELASA) into a biolayer interferometry (BLI) system to develop an automated, high-throughput, real-time monitoring BLI-ELASA biosensing platform. This platform exhibited a wide linear detection window (10–810 pg/mL range) and high sensitivity for GDF15 (detection limit of 5–6 pg/mL). Moreover, we conﬁrmed its excellent performance when applied to GDF15 quantification in real samples from glaucomatous rats and clinical patients. We believe that this technology represents a robust, convenient, and cost-effective approach for risk screening, early diagnosis, and animal modeling evaluation of glaucoma in the near future. Highlights: An aptamer with high affinity, high specificity, and high stability for binding to both human-derived and rat-derived GDF15 was obtained. The molecular mechanism and key driving force underlying the recognition of targets by the aptamer were further elucidated. An automated, high-throughput, and real-time online monitoring BLI-ELASA biosensing platform for GDF15 detection was developed. This technology represents a robust, convenient, and cost-effective approach for risk screening, early diagnosis, and animal modeling evaluation of glaucoma.